2010
DOI: 10.1007/s10725-010-9538-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fruit load, shading, and 9,10-ketol-octadecadienoic acid (KODA) application on MdTFL1 and MdFT1 genes in apple buds

Abstract: The effects of fruit load, shading, and 9, 10-ketol-octadecadienoic acid (KODA) application on the expression of MdTFL1 and MdFT1 genes were investigated in apples (Malus domestica Borkh.). The expression of MdTFL1 in apical buds from 21 to 63 days after full bloom (DAFB) in plants subjected to heavy crop treatment (HCT) was higher than that in plants subjected to flower thinning treatment (FTT). In contrast, the expression of MdFT1 did not show a clear difference between HCT and FTT. The shading treatment inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Nevertheless, a similar reduction in MdTFL1‐1 expression occurred in trees with HFL (Figure g). Using semi‐quantitative RT‐PCR, others have reported an effect of fruit load on this gene's expression in apices of 1‐year‐old shoots (Kittikorn et al ., ). Here, MdTFL1‐1 levels decreased more rapidly in trees with HFL (Figure g); this difference could not explain why these BS apices remain vegetative.…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, a similar reduction in MdTFL1‐1 expression occurred in trees with HFL (Figure g). Using semi‐quantitative RT‐PCR, others have reported an effect of fruit load on this gene's expression in apices of 1‐year‐old shoots (Kittikorn et al ., ). Here, MdTFL1‐1 levels decreased more rapidly in trees with HFL (Figure g); this difference could not explain why these BS apices remain vegetative.…”
Section: Resultsmentioning
confidence: 97%
“…In 'Fuji' apple tree (36° north latitude, 139° west longitude and 747 meter above sea level) found no difference in flowering locus T (MdFT1) gene expression (MiFT homolog) in apical buds of shaded and sunny buds but the expression of MiTFL1 (floral repressor) was higher in shaded shoots (Kittikorn et al, 2011), results that do not coincide with our study, despite results in apple, were obtained in different species and tissue and shading was only 50% and in the present study conducted under field conditions very different from those of apple tree (21° north latitude 105° west longitude, 150 m), at least on the north side, the shade was about 90%.…”
Section: Temperature and Precipitationmentioning
confidence: 99%
“…sombreados (Kittikorn et al, 2011), resultados que no coinciden con nuestro estudio, no obstante los resultados en manzano, se obtuvieron en diferente especie y tejido y el sombreo fue de solo 50%, y en el presente estudio realizado bajo condiciones de campo muy diferentes a las de manzano (21° latitud norte 105° longitud oeste, 150 msnm), al menos de lado norte, el sombreo fue cerca de 90 %.…”
Section: Temperature and Precipitationunclassified
“…A more detailed analysis with narrower sampling intervals will be required for further discussion on the timing. Kittikorn et al (2011) reported that KODA may be related to flower bud formation through its influence on MdTFL1, which is a TFL1 homologue in apple. Our results for PnTFL1b may conflict with what was reported for MdTFL1.…”
Section: Effects Of Koda Application On the Expression Of Flowering-rmentioning
confidence: 99%
“…In particular, the effects of KODA on genes related to flowering are poorly understood. Kittikorn et al (2011) showed the expression levels of the TFL1 homologue, MdTFL1 mRNA, are decreased by KODA application in apple. To the best of our knowledge, this is the only report on changes in gene expression caused by KODA.…”
mentioning
confidence: 96%